Campus tecnológico y universitario de la Orinoquia (2020)
The departament of Arauca currently has a deficit in Higher Education coverage. According to DANE statistics, coverage for 2018 is only 8.8%. This is a worrying figure, since every day fewer young people are willing and table to access an HEI (Higher Education Institution), this hinders the training of professionals who promote the social and economic sector of the departament of Arauca. By means of methodological analysis of social, cultural and economic aspects; urban and regulatory analyses, the intervention of the existing facilities of the CTUO (Orinoquia Technological and University Campus), located in Tame – Arauca, arises as an alternative to this deficit. To this end, a study of educational facilities is being carried out on a global, continental, national and regional scale to determine the lineaments that the project should follow in order to generate a coherent proposal for the needs of the student population, taking into account the natural factors and effects that the property presents. The CTUO project is being developed in order to reduce the existing deficit in Higher Education facilities in the departament, through the proposal of new spaces for the campus, which are designed for the development of educational and related activities, without leaving behind the regional relevance, which is focused on agro-ecology. The urban and architectural proposal seeks a balance with the environment through strategies that reduce energy consumption and the possible negative impact that the equipment and its activities may generate, as well as the possibility of providing comfort in the spaces for the use of young Araucans.